Seasonal effect of dietary energy and protein level on the performance of growing guinea fowl (Numida meleagris) - MANDAL, A B; PATHAK, N N (The Indian Journal of Animal Sciences, 2014)
An experiments, with varying levels of dietary energy and protein, was conducted to assess the yield and chemical cumposition of meat of 3 varieties (pearl, lavender and while) of growing guinea fowl at 12 weeks of age. Nine dietary treatments combining 3 levels of protein and metabolizable energy (ME) in a factorial design were offered during each growth phase Le. 0-4,5-8 and 9-12 weeks of age. The levels of protein (%) were 24, 22 and 20-P1 : 22, 20 and 18-P2 and 20, 18 and 16-P3, respectively, with ME concentrations: 12.13 MJ (2800 keal) and -12.55 MJ (3000 k cal)-E1, 11.30 MJ (2700 k cal) and 11.72 MJ (2800 k cal) -E2-12 and, 10.46 (2500 k cal) and 10.88 MJ (2600 k calli kg-E), respectively, for the respective growth phases. After completion of 12 weeks of age, 30 birds (10 of each variety) were sacrificed to evaluate carcass traits and composition of thigh and breast muscles. The live weight at 12 weeks of age differed due to dietary levels of energy and protein. Live weights were higher (P<0.05) in high energy (E1) level than E2 or E3. Mean live weights in P1 and P2 were similar but lesser live weight was recorded in P3. The variety white grew better (P<0.05) than the other two varieties. The eviscerated yield was lesser in low energy or low protein diets. Protein contents of breast muscle decreased in low energy (E3) group. In thigh muscles protein content decreased while fat content increased in high and medium level of energy in diets in comparison to low dietary energy. The optimum dietary energy requirement as per the present experiment was 12.13 MJ (2900 kca!), 12.55 MJ (3000 kcal) ME and 12.55 MJ (3000 kcal) ME per kg diet with 24, 20 and 18% CP during 0-4, 5-8 and 9-12 weeks of growth phases, respectively, for meat production of growing guinea fowls during cold season.